Properties of PVA Hydrogel Wound‐Care Dressings Containing UK Propolis. Issue 1 (October 2016) - Oliveira, Renata N.; McGuinness, Garrett B.; Ramos, Maria Eduarda T.; Kajiyama, Carolina E.; Thiré, Rossana M. S. M.
Summary: Burns pose a potential threat to health, and often require dressings. PVA hydrogels present many characteristics of ideal dressings, but do not have any intrinsic antimicrobial properties. Propolis is a natural antimicrobial substance that can be incorporated in materials intended for wound‐care. The goal of this work was to produce and characterize (in terms of swelling behaviour, microstructural and thermal analysis) PVA gels loaded with a UK propolis. Propolis was loaded in the gels and it altered the crystallinity of the PVA gels. The thermal profile of the PVA‐UK propolis gels was different from that of PVA gel alone. All gels presented at least ∼200% of swelling degree. Weight loss as well as propolis release was high for samples with high amount of propolis. Samples with the highest amount of propolis still presented mechanical properties adequate for the application.